2022
DOI: 10.1002/clt2.12134
|View full text |Cite
|
Sign up to set email alerts
|

Allergen immunotherapy during the COVID‐19 pandemic—A survey of the German Society for Allergy and Clinical Immunology

Abstract: Background: When the coronavirus pandemic 2019 (COVID-19) emerged, concerns were also raised regarding the safety of allergen immunotherapy (AIT). The German Society for Allergology and Clinical Immunology (DGAKI) conducted a survey to collect real-world data on the daily routine of administering subcutaneous AIT (SCIT) and sublingual AIT (SLIT) during the COVID-19 pandemic.Methods: A web-based retrospective survey using the online platform survio with 26 standardized questions was used to survey physicians tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“… 198 During COVID‐19, AIT was initiated and continued by most physicians in patients without indications of SARS‐CoV‐2 infection. 199 In contrast, lockdown during COVID‐19 resulted in decreased numbers of patients initiating AIT but without significant impact on sublingual immunotherapy. 200 …”
Section: Management Of Allergic Diseases During the Covid‐19 Pandemicmentioning
confidence: 99%
See 1 more Smart Citation
“… 198 During COVID‐19, AIT was initiated and continued by most physicians in patients without indications of SARS‐CoV‐2 infection. 199 In contrast, lockdown during COVID‐19 resulted in decreased numbers of patients initiating AIT but without significant impact on sublingual immunotherapy. 200 …”
Section: Management Of Allergic Diseases During the Covid‐19 Pandemicmentioning
confidence: 99%
“…Dupilumab seems to be safe and crucial for a better outcome of COVID‐19 and should be continued in AD patients during the COVID‐19 pandemic 198 . During COVID‐19, AIT was initiated and continued by most physicians in patients without indications of SARS‐CoV‐2 infection 199 . In contrast, lockdown during COVID‐19 resulted in decreased numbers of patients initiating AIT but without significant impact on sublingual immunotherapy 200 …”
Section: Management Of Allergic Diseases During the Covid‐19 Pandemicmentioning
confidence: 99%
“…Current studies demonstrated adherence by clinicians to national and international position papers and guidelines of allergen immunotherapy during the COVID-19 pandemic worldwide. Besides, several surveys/research have shown good tolerability of allergen immunotherapy for both subcutaneous and sublingual-oral forms [18].…”
Section: Asthmamentioning
confidence: 99%
“…In addition, straightforward and consensus-based recommendations for both SCIT- and SLIT-treated patients have been proposed internationally [ 69 ] and have also been adapted to the situation in German-speaking countries [ 70 ]. However, a high grade of heterogeneity of adherence to the academic guidance given has been found in international [ 71 ] and national [ 72 ] surveys on COVID-19 and AIT suggesting some undertreatment of patients.…”
Section: Ait During the Covid-19 Pandemicmentioning
confidence: 99%